(untitled) (Mustansiria Dental Journal, 2018)
Iraqi populations in Maysan general hospital (Maysan -Iraq) and compare this prevalence with other international studies. Data of this study were obtained from reports of patients diagnosed with odontogenic cysts between 2007 and 2010. Case records of patients who fit the Histological Classification of the World Health Organization (2005) were included. The following variables were analyzed: gender, age group, anatomical location and histological type. Odontogenic cysts accounted for 90 % of all lesions biopsied throughout the study period. Pain feeling and clinical expansion were recorded in most of our patients. Mean patient age was (28) years and (61%) of the patients were males. Radicular cyst was the most prevalent histological type (28.75%), followed by odontogenic keratocyst (25%) then dentigerous cyst (23.75%). The mandible was the most prevalent site of the lesions (55%). Odontogenic cysts appear to have a distinct predilection for the male gender, the third decade of life and are more frequent in the mandible. Awareness about the prevalence and characteristics of odontogenic cysts is important in primary diagnosis and treatment of these lesions.